Whatsapp Group: Media Komunikasi Orang Tua Dan Guru - Yana, Fitri; Inayatillah, Inayatillah; Agustina, Maya (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2021)
With the development of technology and the emergence of various communication platforms, interaction can become easier. Especially in the online learning period, almost 90% of educational and non-educational interactions are carried out through WhatsApp Groups. The purpose of this paper is to find out directly the use of WhatsApp Groups in building communication between parents and teachers and to find out the obstacles faced by parents and teachers in using WhatsApp Groups at SD IT Teuku Umar. This type of research is field research (field research). Data collection techniques used are interviews and documentation. The data analysis technique used is descriptive analysis. The results showed that the use of WhatsApp Group was used as a means to support student learning activities outside of school hours. So that it will make children enthusiastic about learning when they are at home. The obstacles faced by parents and teachers in the use of WhatsApp Groups are in the technical part, namely the package quota runs out and internet network disturbances, the ethics of using groups in the WhatsApp Group application, the lack of response from students' parents due to their busy lives and there are still parents who do not understand the information. given from the teacher to the parents of students